Synonymic and hypero-hyponymic paradigm of the delimitation between media discourse and mass communication media discourse - Shishkin, B. A. (Гуманитарные и юридические исследования, 2024)
Introduction. Modern Russian media studies are characterized by a special property, namely the pluralization of opinions in the interpretation of the basic term for the discipline – media. The discrepancy in its interpretation is due to the existence of differential paradigms for understanding lexicalsemantic correlation with such a term as mass communication media: synonymic and hypero-hyponymic. As a result, this situation creates a number of obstacles for Russian media discourse and mass communication media discourse researchers to achieve a comprehensive understanding of their essence, which naturally actualizes the research problem. Therefore, in this article we set ourselves the goal of delimiting the two discourses from the angle of the synonymic and hypero-hyponymic paradigm. Materials and Methods. The empirical material of the article included both Russian and foreign studies, monographic works, explanatory dictionaries, as well as textbooks in the field of media. In addition to general scientific research methods, the basis of the work was hermeneutic analysis, namely the lexical-hermeneutic technology of analysis. This technology was deepened through two methods: definitional analysis of dictionary entries and structuralnoematic method. Analysis. The research consisted of four stages, illustrating the relationships of the structural elements of the textual communication model. Firstly, social reality and its connection with the consciousness of the author were explored. Secondly, the connection between the author’s consciousness and language was characterized. Thirdly, the languagebased production process of texts and its further addressing to the recipient (other researchers) was analyzed. Fourthly, existing ways of adjusting the interpretation of the terms media and mass communication media were demonstrated. Results. The research results show a clear manifestation of the synonymic paradigm in the Russian scientific space, which can manifest itself in various disciplines. Moreover, the hypero-hyponymic paradigm is characteristic of foreign research and more narrow-profile Russian work. The use of both approaches and their combination generates a complex system that can describe not only high-level components of media discourse, but also low-level concepts of mass communication media discourse.